Predictors of the Perceived Efficacy of Actions Against Austerity Measures. Issue 1 (5th April 2017) - Poeschl, Gabrielle; Valentim, Joaquim P.; Papastamou, Stamos; Chryssochoou, Xenia; Prodromitis, Gerasimos; Pavlopoulos, Vassilis; Mari, Silvia; Volpato, Chiara
In this paper, we analyse the responses of 450 students from Greece, Portugal and Italy, who were asked to assess the efficacy of 32 actions as reactions against the austerity measures implemented to deal with the financial and economic crisis. These actions were organized into six types by a principal component factor analysis, and were ranked as follows from the most effective to the least effective: protectionism, civic participation, political resistance to government measures, individual financial protection, economic resistance to government measures and violence. Results showed that Greek respondents, who were in the most difficult socioeconomic situation, viewed all types of actions, except civic participation and individual financial protection, as more effective than the other respondents did. Regression analyses revealed, however, that crisis-related variables, in particular, the attribution of responsibility for the crisis to internal factors and not to the people, and individual-related variables, such as political orientation and the intensity of depressive feelings, were strong predictors of the assessment of the efficacy of actions, in addition to the socioeconomic situation of the countries.